2014
DOI: 10.1016/j.gaitpost.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Postural strategies assessed with inertial sensors in healthy and parkinsonian subjects

Abstract: The present study introduces a novel instrumented method to characterize postural movement strategies to maintain balance during stance (ankle and hip strategy), by means of inertial sensors, positioned on the legs and on the trunk. We evaluated postural strategies in subjects with2 types of parkinsonism: idiopathic Parkinson's disease (PD) and Progressive Supranuclear Palsy (PSP),and inage-matched control subjects standing under perturbed conditions implementedby the Sensory Organization Test (SOT).Coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 29 publications
1
41
0
2
Order By: Relevance
“…To date this is the largest study examining PC in PD and healthy older controls (n = 57) with an instrumented balance test (previous studies ranged on average from n = 19 to n = 40 [2,[16][17][18][19]27]). The novel findings of this study were that PC changes during the first 30 seconds of a test in healthy controls after which it is maintained, in contrast to PD who did not show early time-dependent change in PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date this is the largest study examining PC in PD and healthy older controls (n = 57) with an instrumented balance test (previous studies ranged on average from n = 19 to n = 40 [2,[16][17][18][19]27]). The novel findings of this study were that PC changes during the first 30 seconds of a test in healthy controls after which it is maintained, in contrast to PD who did not show early time-dependent change in PC.…”
Section: Discussionmentioning
confidence: 99%
“…To do this we used autocorrelations of squared values of the acceleration traces and squared first-derivative of the acceleration traces (the precursors of RMS and Jerk values, respectively). Averaged autocorrelation values showed that a 2 second bout was optimal with correlation values dropping to zero after no more than a lag of 100 samples (2 seconds), this choice took also into account the frequency components of the signal [2]. Therefore outcomes for PC strategies were calculated during consecutive non-overlapping 2 second windows (i.e.…”
Section: Data Considerationsmentioning
confidence: 99%
“…Analyzing quiet stance in different body strategies could have also been beneficial because the postural control system is more complex than an inverted pendulum and behaves like a multilink pendulum (Creath, Kiemel, Horak, Peterka, & Jeka, 2005). Although postural control should be analyzed as a multilink pendulum, it has been shown that PD patients do not use a hip strategy, because they have small responses, stiff postural coordination, and impaired proprioception (Baston, Mancini, Schoneburg, Horak, & Rocchi, 2014). Thus, the placement of reflective markers on the shoulder and the ankle was appropriate to quantify postural sway variability as an inverted pendulum (Suarez et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Difference of estimated step length and gold standard measure is below 5% when considering median values. Baston et al (2014) introduced an instrumented method to characterize postural movement strategies to maintain balance during stance (ankle and hip strategy), by means of inertial sensors positioned on the legs and on the trunk. Coordination between the upper and lower segments of the body during postural sway was measured using a covariance index over time [318].…”
Section: Inertial Sensorsmentioning
confidence: 99%
“…Baston et al (2014) introduced an instrumented method to characterize postural movement strategies to maintain balance during stance (ankle and hip strategy), by means of inertial sensors positioned on the legs and on the trunk. Coordination between the upper and lower segments of the body during postural sway was measured using a covariance index over time [318]. They also measured the amount of postural sway, as adjunctive information to characterize balance, by the Root Mean Square (RMS) of the horizontal trunk acceleration signal showing that control subjects were able to change their postural strategy, whilst PD subjects persisted in use of an ankle strategy in all conditions.…”
Section: Inertial Sensorsmentioning
confidence: 99%